High-calcium tuna bone meal cookies improve linear growth in stunted toddlers - Rifzul Maulina; Eka Diah Kartiningrum; Dian Pitaloka Priasmoro (Nursing and Health Sciences Journal (NHSJ), 2026)
Stunting remains a critical public health challenge in Indonesia, necessitating innovative, locally sourced nutritional interventions. Tuna fish bones represent an underutilized source of bioavailable calcium and essential nutrients. This study evaluated the efficacy of high-calcium tuna bone meal cookie supplementation in improving the nutritional status of stunted toddlers. A quasi-experimental pretest–posttest control group design was conducted in Bandungrejosari Regency, Indonesia. Thirty-two stunted toddlers aged 12–60 months were recruited through purposive sampling and allocated into intervention (n=16) and control (n=16) groups. The intervention group received tuna bone meal cookies twice daily for 60 consecutive days, while the control group received no supplementation. Anthropometric measurements were obtained at baseline and post-intervention. Data were analyzed using independent and paired t-tests, with α=0.05. The intervention group demonstrated significantly greater linear growth compared to controls, with a mean height difference of 4.53 cm (p=0.008). Post-intervention mean height was 96.00 cm in the intervention group versus 91.47 cm in the control group. Tuna bone meal cookie supplementation significantly improves nutritional status and linear growth among stunted toddlers. This cost-effective, sustainable intervention using marine by-products shows promise for integration into community-based stunting-reduction programs